Facile Preparation and Properties Study of CL-20/TATB/VitonA Composite Microspheres by a Spray-Drying Process. (7th April 2020) - Hou, Conghua; Li, Congcong; Jia, Xinlei; Zhang, Yuanping; Zhang, Shimin
Abstract : To improve the safety of ammonium nitrate explosives, a one-step method involving the formation of CL-20/TATB/VitonA composite microspheres using spray drying is presented. The crystal morphology, particle size, crystal structure, thermal properties, and sensitivity of raw materials of CL-20 and TATB, CL-20/VitonA particles, and CL-20/TATB/VitonA microspheres were characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD), differential scanning calorimetry (DSC), and impact and friction sensitivity tests. The SEM results show that the prepared CL-20/TATB/VitonA composites with micro-/nanoscale grain size have a good spherical shape. Thermal analysis data show that TATB coating enhances the thermal stability of CL-20/VitonA. The impact and friction sensitivity results show that superior mechanical properties of these composite microspheres could be maintained. Obviously, this approach is an effective desensitization technique to prepare composite microspheres for explosives.